2012
DOI: 10.1128/jvi.00980-12
|View full text |Cite
|
Sign up to set email alerts
|

Cyclophilins Facilitate Dissociation of the Human Papillomavirus Type 16 Capsid Protein L1 from the L2/DNA Complex following Virus Entry

Abstract: Human papillomaviruses (HPV) are composed of the major and minor capsid proteins, L1 and L2, that encapsidate a chromatinized, circular double-stranded DNA genome. At the outset of infection, the interaction of HPV type 16 (HPV16) (pseudo)virions with heparan sulfate proteoglycans triggers a conformational change in L2 that is facilitated by the host cell chaperone cyclophilin B (CyPB). This conformational change results in exposure of the L2 N terminus, which is required for infectious internalization… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
159
1
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 96 publications
(163 citation statements)
references
References 69 publications
2
159
1
1
Order By: Relevance
“…Other laboratories showed that L1 dissociates from L2 during HPV entry and is sorted to the lysosome for degradation (39). We found that some L1, like L2, remains physically associated with the retromer and traffics to a Golgi-like compartment.…”
Section: Discussionmentioning
confidence: 55%
“…Other laboratories showed that L1 dissociates from L2 during HPV entry and is sorted to the lysosome for degradation (39). We found that some L1, like L2, remains physically associated with the retromer and traffics to a Golgi-like compartment.…”
Section: Discussionmentioning
confidence: 55%
“…For example, herpesviruses and adenoviruses both egress into the cytoplasm, yet protect their viral DNA by keeping it encased in viral capsids until directly transferring it into the nucleus through the nuclear pore complex. In contrast, the capsid is unlikely to protect papillomavirus (PV) genomes while traversing the cytoplasm, because the major capsid protein is lost in the endocytic compartment (2).…”
mentioning
confidence: 99%
“…Following primary attachment and internalization, acidification of early endosomes triggers capsid disassembly (7-22). Host cell cyclophilins release the majority of L1 from the L2 protein, which remains in complex with the viral genome (2,23,24). A large portion of the L2 protein translocates across the endocytic membrane to engage factors, including the retromer complex, dynein, sorting nexins, and rab GTPases, that mediate transport to the trans-Golgi network (TGN) (25)(26)(27)(28)(29)(30)(31)(32)(33)).…”
mentioning
confidence: 99%
“…CypA interacts with viral proteins supporting viral replication 69 . CypA inhibitors such as cyclosporine A (CsA) have been shown to inhibit the replication of HIV, HCV, influenza virus, CoV, HBV, HSV, human cytomegalovirus (HCMV), VSV, vaccinia virus (VV) and human papillomavirus (HPV) [105][106][107][108][109][110][111][112][113][114] . Alisporivir (Debio-025) and SCY-635, both CsA analogues, have shown antiviral activity against HCV in vivo and are currently in combination with other anti-HCV compounds in various clinical trials 115,116 .…”
Section: Targeting Common Host-factors Used For Viral Replicationmentioning
confidence: 99%